Comparativo de comunicação de micros serviços desenvolvidos em múltiplas linguagens de programação - Chaves, Lucas Martins (2024)
How microservices communicate is fundamental to the overall performance of a system. Therefore, there are various protocols and communication methods available in different programming languages. With this in mind, this work presents a testing model to identify performance behaviors among different communication methods applied to multiple languages. For this purpose, Elastic Stack observability resources are used to collect data and create visualizations of load tests generated with the K6 tool. To be subjected to the tests, three applications were developed in Go, JavaScript, and Python, implementing REST, gRPC, and GraphQL. The results show overall better performance in Go, superior performance of GraphQL for insertions, and similar behavior between GraphQL and REST, with a slight advantage for REST in handling large volumes of data.